Crack Width Investigation of Trapezoidal Precast Segmental Foundation - Rasidi, Nawir; Mudjanarko, Sri Wiwoho; Novianto, Dandung (International Journal of Sustainable Construction Engineering and Technology, 2020)
Maximum Crack width prediction formula proposed by various researcher indicates that each formula contains a different set of variables. This research presents a crack width investigation of trapezoidal precast segmental foundation under static loading. A literature review also suggests that there is no general agreement among various researcher on the relative significance of different variables affecting the crack width, despite the large number of experimental work carried out during the past few decades. An analytical method is developed to determine the concrete stress distribution near flexural cracks in reinforced concrete foundation and used to investigate the effects of various variables on width of cracks. The new formula is developed using a large number of curvature values calculated from the concrete and steel strains at various sections between adjacent cracks for a number of trapezoidal precast segmental foundation. The present method of incorporating the tension stiffening effect is verified by comparing calculated fracture mechanic and those measured by other researcher. The curvature values at sections between adjacent cracks are calculated using an empirical formula. Development of this formula is based on the curvature values calculated using the concrete and steel strains at various sections between successive cracks, for a number of composite precast foundation. Using the curvature values evaluated by the proposed formula, short-term deflections were determined for a large number of flexural members and the results were compared with those measured by other researcher. This comparison indicated that the present method of incorporating the tension stiffening effect in fracture mechanic calculations is acceptable. The results of this investigation showed that cracking was common for the bottom of precast segmental foundation under static loading; however, the crack width was usually within the design limits.